EXPLORING INTEGRATION OF TRADITIONAL RETAILERS IN THE AGRI-FOOD SUPPLY CHAIN: CASE STUDY OF POULTRY SUPPLY CHAIN IN BANDUNG - Fitri Larasati, Puti
Traditional retailers have a crucial role in distributing smallholder products to consumers in the agri-food supply chain. In the face of changing market landscape with higher customers demand, these retailers continue to operate within an informal structure with traditional management approaches and limited resource. Their integration and coordination in the agri-food supply chain are expected to improve their survival rate in this evolving environment. However, extant literature on supply chain integration predominantly focuses on existing integration of largescale and more established supply chain actors. Limited studies have been done on how to effectively integrate small-scale actors. Furthermore, significant gaps exist due to past neglection of traditional retailers in the agri-food supply chain integration literatures. This knowledge gaps necessitates further investigation of agri-food supply chain integration, with specific focus on traditional retailers in developing economies.